Amisulpride and olanzapine followed by open-label treatment with clozapine in first-episode schizophrenia and schizophreniform disorder (OPTiMiSE): a three-phase switching study. (October 2018) - Kahn, René S; Winter van Rossum, Inge; Leucht, Stefan; McGuire, Philip; Lewis, Shon W; Leboyer, Marion; Arango, Celso; Dazzan, Paola; Drake, Richard; Heres, Stephan; Díaz-Caneja, Covadonga M; Rujescu, Dan; et al.
Summary: Background: No established treatment algorithm exists for patients with schizophrenia. Whether switching antipsychotics or early use of clozapine improves outcome in (first-episode) schizophrenia is unknown. Methods: This three-phase study was done in 27 centres, consisting of general hospitals and psychiatric specialty clinics, in 14 European countries and Israel. Patients aged 18–40 years who met criteria of the DSM-IV for schizophrenia, schizophreniform disorder, or schizoaffective disorder were treated for 4 weeks with up to 800 mg/day amisulpride orally in an open-label design (phase 1). Patients who did not meet symptomatic remission criteria at 4 weeks were randomly assigned to continue amisulpride or switch to olanzapine (≤20 mg/day) during a 6-week double-blind phase, with patients and staff masked to treatment allocation (phase 2). Randomisation was done online by a randomisation website; the application implemented stratification by site and sex, and applied the minimisation method for randomisation. Patients who were not in remission at 10 weeks were given clozapine (≤900 mg/day) for an additional 12 weeks in an open-label design (phase 3). The primary outcome was the number of patients who achieved symptomatic remission at the final visits of phases 1, 2, and 3, measured by intention-to-treat analysis. Data were analysed with a generalised linear mixed model, with a logistic link and binomial error distribution. This trial is registered withClinicalTrials.gov, numberNCT01248195, and closed to accrual. Findings: Between May 26, 2011, and May 15, 2016, we recruited 481 participants who signed informed consent. Of the 446 patients in the intention-to-treat sample, 371 (83%) completed open-label amisulpride treatment, and 250 (56%) achieved remission after phase 1. 93 patients who were not in remission continued to the 6-week double-blind switching trial, with 72 (77%) patients completing the trial (39 on olanzapine and 33 on amisulpride); 15 (45%) patients on amisulpride versus 17 (44%) on olanzapine achieved remission (p=0·87). Of the 40 patients who were not in remission after 10 weeks of treatment, 28 (70%) started on clozapine; 18 (64%) patients completed the 12-week treatment, and five (28%) achieved remission. The number of serious adverse events did not differ between the treatment arms in phase 2: one patient on olanzapine was admitted to hospital because of an epileptic seizure, and one patient on amisulpride was admitted to hospital twice because of exacerbations of psychotic symptoms. Over the course of the trial, two serious suicide attempts were reported. Interpretation: For most patients in the early stages of schizophrenia, symptomatic remission can be achieved using a simple treatment algorithm comprising the sequential administration of amisulpride and clozapine. Since switching to olanzapine did not improve outcome, clozapine should be used after patients fail a single antipsychotic trial—not until two antipsychotics have been tried, as is the current recommendation. Funding: European Commission Seventh Framework Program.